Suffusion restraint in gap-graded soil reinforced with fibers - Teng, Yao-Zong; Chen, Xiu-Liang; Chen, Liang; Hu, Liang; Gu, Jia-Hui; Yin, Zi-Xue; Lu, Zhou-Zhou (Frontiers in Earth Science, 2022)
To study how gap-graded soil reinforced with fibers of different types restrains suffusion in embankment dams, the hydraulic response of fiber-reinforced soil (FRS) containing polypropylene fibers (PPF), coir fibers (CF) or basalt-tape fibers (BTF) was investigated in one-dimensional seepage tests. The critical hydraulic gradient and fine-particle loss of the FRS were analysed quantitatively by changing the fiber type, fiber content, and reinforcement-layer thickness. The test results show that the three types of FRS all had restraining effect on the development of suffusion. The netting reinforcement effect of PPF was the best, followed by the water absorption and expansion of CF to reduce pore volume, and finally the effect of BTF was to block migration channels under the same reinforcement conditions. With increasing fiber content and the reinforcement-layer thickness, the critical onset hydraulic gradient (icr,onset), and critical failure hydraulic gradient (icr,failure) increased, improving the internal erosion resistance of gap-graded soils against suffusion. The fine-particles loss decreased and the restraint rate of fine-particle loss (RF) increased meant that the permeability stability of soil was enhanced. Linear regression analysis showed that the reinforcement-layer thickness has greater influence on restraining effect parameters than fiber content.